تأثير تطبيق الضمادات الجافّة وضمادات العسل على التئام قرحات القدم السكرية من الدرجة الأولى والثانية - قنجراوي, أكثم; حيدر, مازن; العبدو, يحي (Latakia University Journal -Medical Sciences Series, 2013)
تعد قرحات القدم السكرية من المضاعفات الخطيرة التي ترتبط بالداء السكري، تتطلب هذه القرحات رعاية طبية وتمريضية، تبدأ بتحديد درجة القرحة، وتطبيق الضماد الذي يعد من مسؤوليات الممرض. يوجد عدة أنواع لضماد القرحات ذات الدرجة الأولى والثانية ومنها الضماد الجاف وضماد العسل. هدف البحث: تقييم تأثير تطبيق الضماد الجاف وضماد العسل على التئام قرحات القدم السكرية من الدرجة الأولى والثانية. مواد البحث وطرائقه: تمت الدراسة في مركز الداء السكري باللاذقية, على عينة مؤلفة من أربعين مريضاً بالغاً حققوا خصائص العينة, وقُسّمت عشوائيا إلى مجموعتين بالتساوي، الأولى: خضعت لتطبيق تقنية الضماد الجاف، والثانية: تطبيق تقنية ضماد العسل، وتم تغيير الضماد لمدة ستة أسابيع. نتائج البحث: أظهرت النتائج أنّ نسبة (45%) حققوا التئاماً تاماً، و(35%) التئاماً جزئياً و (20%) عدم التئام في المجموعة الأولى، في المجموعة الثانية: (85%) حققوا التئاماً تاماً، و(15%) التئاماً جزئياً. الاستنتاجات: كان تطبيق ضماد العسل أكثر فعالية بدلالة إحصائية من تطبيق الضماد الجاف في التئام قرحات القدم السكّرية من الدرجة الأولى والثانية. The diabetic foot ulcers considers a serious complications that related to diabetes, ulcers required medical and nursing care, that started with determine the degree of ulcer and applying Dressing which is from responsibility of nurses. There are many kinds of dressing for grade 1&2 diabetic foot ulcers such as dry and honey dressings. Aim of the study: Assessment the effect of applying the dry and honey dressings on the healing of grade (1&2) diabetic foot ulcers. Material and Methods: The study conducted in the Diabetes Mellitus Center in Lattakia city. A convenient sample of 40 adult diabetic patients whose meet the sample selection criteria were chosen. The sample divided randomly to two equal groups, either the first group who subjected to dry dressing technique, or to the second group who subjected to honey dressing technique. Dressing changed for six weeks. Results: At the end of the study: (55%) of patients had complete ulcer healing, (35%) had partial healing and (20%) had no ulcer wound healing in the dry dressing group. Whereas (85%) of patients had complete ulcer healing and (15%) had partial healing. Conclusions: Honey dressing had statistical significant effects on the healing of grade (1&2) diabetic foot ulcers.